ISLAMIC EDUCATION CONSTRUCTION RAHMATAN LIL'ALAMIN IN THE PERSPECTIVE OF ISLAMIC RELIGIOUS FIGURES IN MALANG - Ali Mukhammad Abrori (Universitas Islam Malang, 2022)
The Islamic Society of Malang, has pattern various forms of worship and da'wah . Diversity this , in one aside bring goodness , because with diversity that , will add treasure science islam . Diversity method worship as well as a model of da'wah , can cause internal divisions of Muslims , if no be addressed by wise and wise . As effort ward off affiliated Islamic movement with radicalism and takfiri, some religious leaders in Malang indeed must campaign Rahmatan's Islamic Da'wah Lil'Alamin . In this case , there are several problems that are the focus of research as well as destination in research , namely (1) What is the view of Malang Islamic religious leaders about the concept of Islamic education Rahmatan Lil'Alamin? (2) How is the process of adapting the Islamic religious leaders in Malang, carrying out the process of realizing the teachings of love in the context of Rahmatan Lil'Alamin's Islamic education? (3) How do Islamic religious leaders in Malang carry out the process of internalizing the values of Rahmatan Lil'Alamin's Islamic education? . For that in writing dissertation this , author use type approach qualitative. From result study this that the figures have differences and similarities in views about the definition and concept of Islamic education Rahmatan Lil'Alamin . Meanwhile, the points of similarity regarding Rahmatan Lil'Alamin's concept of Islamic education are: Muslim leaders agree that every human being must spread love to all of God's creatures. Every citizen of different ethnicity, religion, race, and class, must live, tolerate each other, love one another. In the midst of the diversity of sects and understandings, Islamic religious leaders have carried out a process of adjustment and embodiment in relation to Rahmatan Lil'Alamin's Islamic education. In relation to the internalization process, how these figures provide real guidance to the Muslim community, in relation to Rahmatan Lil'Alamin's Islamic education.Keywords:Ã‚Â Islamic Education Construction, Rahmatan Lil'Alamin, Perspective Islamic religious figures.